2015
DOI: 10.1063/1.4932202
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum ultra-violet damage and damage mitigation for plasma processing of highly porous organosilicate glass dielectrics

Abstract: Porous organosilicate glass thin films, with k-value 2.0, were exposed to 147 nm vacuum ultra-violet (VUV) photons emitted in a Xenon capacitive coupled plasma discharge. Strong methyl bond depletion was observed, concomitant with a significant increase of the bulk dielectric constant. This indicates that, besides reactive radical diffusion, photons emitted during plasma processing do impede dielectric properties and therefore need to be tackled appropriately during patterning and integration. The detrimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“… 37 , 38 , VUV emission between 100 nm and 190 nm is the most damaging for Si-CH 3 bonds in the bulk low-k material. As shown in literature 12 , 39 , pure SF 6 does emit in the VUV range.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“… 37 , 38 , VUV emission between 100 nm and 190 nm is the most damaging for Si-CH 3 bonds in the bulk low-k material. As shown in literature 12 , 39 , pure SF 6 does emit in the VUV range.…”
Section: Discussionsupporting
confidence: 55%
“…Damage evolution by VUV is modeled using the equation 37 : where σ PA is the photo-absorption cross section, ϕ is an adjustment parameter allowing to consider the effective CH 3 out-diffusion, [Si] is the Si concentration into the low-k, and I 0 is the radiation intensity. Typical SF 6 plasma emission spectrum in VUV range is shown in references 12 , 39 . The continuous emission in 100 nm to 150 nm range with local maxima (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This metallization route relies on first patterning the dielectric layer via anisotropic plasma etching before Cu electroplating and planarization. Plasma-induced damage of new potential low-k materials, especially porous ones, during this patterning step is a major roadblock to achieve k -values < 2.4 11,12 . An alternative metallization approach is to first pattern a sacrificial layer that can be removed after the formation of metal interconnect wires, leaving the latter as a patterned top layer 13 .…”
Section: Introductionmentioning
confidence: 99%
“…So, strong reduction of plasma damage, especially in the films with high porosity ( P > 30%) was shown, but the remaining damage close to 20 nm is still observed . The detailed study of plasma damage in low‐k films filled by sacrificial polymers was also carried out . It was shown that the low‐k damage by VUV light cannot be completely avoided even when the pores completely filled with the sacrificial polymer.…”
Section: Introductionmentioning
confidence: 99%